Criminology and Legal Study of Lesbian, Gay, Bisexual and Transgender (LGBT) Actors in Semarang City - Sari, Adinda Novita; Maharani, Ayu Chintya; Amalinda, Ade Rania; Amanda, Yunda Rana (Law Research Review Quarterly, 2020)
The tendency of the community in assessing the existence of LGBT in social life that tends to be pro, contra or even do not care. This research is literature review and field data using relevant theoretical references, namely criminology. According to a criminological perspective, how LGBT which is a deviation is seen as a crime or not. The existence of legal rules to regulate LGBT in relation to the protection of LGBT individuals. This study aims to determine what factors are behind LGBT individuals becoming part of LGBT and LGBT views in criminology and the community's response to the existence of LGBT. This researcg used a normative empirical with a qualitative approach using descriptive narrative research design and using In Depth Interviews to obtain research data. The results of this research indicate that many people do not care about LGBT. It is highlighted that LGBT is not a crime, it will be a crime if it violates the positive laws in force in Indonesia. The rsearch indicated that many people do not care about LGBT. The conclusion from this research is that LGBT is not a crime, it will be a crime if it violates the positive laws in force in Indonesia.